whisky-Jack (or whisky-Johnnie) (1970)
whisky-Jack (or whisky-Johnnie) [ The Labrador jay] This "whisky-Jack" or "whisky-Johnnie", the Indians _ouicheat-chan_, is ofen the only feathered creature one can discover in the thick forest. PRINTED ITEM G.M. Story JUL 1970 JH AUG 1970 Not used Not used Withdrawn withdrawn but no stamp